2008
DOI: 10.4049/jimmunol.180.5.2999
|View full text |Cite
|
Sign up to set email alerts
|

Rat CD4+CD8+ Macrophages Kill Tumor Cells through an NKG2D- and Granzyme/Perforin-Dependent Mechanism

Abstract: We previously identified a subpopulation of monocyte/macrophage lineage cells expressing both CD4 and CD8. This subpopulation was expanded in rat peripheral blood and spleen after immunization with adjuvants containing killed tuberculosis germs. CD4+CD8+ monocytes/macrophages obtained from preimmunized rats exhibited a Th1-type cytokine/chemokine profile, expressed high levels of Fas ligand, perforin, granzyme B, and NKR-P2 (rat ortholog of human NKG2D), and killed certain tumor cells. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…We found that approximately 91% of the CD45 pos cells were double positive for CD45 and F4/80 (a macrophage marker; Figure 2D, II), and approximately 16.1% of the population was double positive for CD45 and CD3 (T cell marker; Figure 2D, III). Of note, cells that express both macrophage and lymphoid markers have been described, which explains why we observed a small fraction of cells that are both F4/80 pos and CD3 pos (36).…”
Section: Assessing the Quality Of The Macs-based Protocolmentioning
confidence: 68%
“…We found that approximately 91% of the CD45 pos cells were double positive for CD45 and F4/80 (a macrophage marker; Figure 2D, II), and approximately 16.1% of the population was double positive for CD45 and CD3 (T cell marker; Figure 2D, III). Of note, cells that express both macrophage and lymphoid markers have been described, which explains why we observed a small fraction of cells that are both F4/80 pos and CD3 pos (36).…”
Section: Assessing the Quality Of The Macs-based Protocolmentioning
confidence: 68%
“…Whether the classical method by which macrophages enact ADCC (phagocytosis by the zipper mechanism 46,47 ) is available on the scale required remains to be determined. An observation of NK-type extracellular killing (utilizing granzymes and perforin) performed by a subset of rat macrophages has been recorded 48 but no similar reports have been found. Hubert et al 22 have described synapses formed in mice, during tumor rejection, between antibody-coated tumor cells and macrophages or neutrophils.…”
Section: What Is the Cytotoxic Mechanism Destroying Antibodycoated Cementioning
confidence: 98%
“…Although further study is necessary to clarify how such molecular alteration was directly involved in a failure of C. trachomatis replication, such mutant cells are potentially useful for elucidating the interaction of pathogenic chlamydiae with lymphocytes. In addition, recent works using animals revealed that granzyme was expressed and produced not only in T cells or NK cells, but also in macrophages, although a counterpart in humans is yet to be discovered [41,42].…”
Section: Kubo T Et Almentioning
confidence: 99%